ORAL CANCER IN PRIMARY HEALTH CARE: AN INTEGRATED APPROACH TO EARLY DIAGNOSIS - de Carvalho, Maria Josilaine das Neves; da Silva, Marcos Gustavo Oliveira; Barbosa, Camila Ramos; Soares, Daiane Caroline Torres; de Lima, Edlla Eracelly Costa; da Silva, Francisco José Macêdo; da Silva, Giseli Cordeiro; da Silva, João Victor Santos; da Silva, Lorena de Jesus Lourenço; da Silva, Pedro Henrique; Arruda, Raynnara Souza; Torres, Vanessa Vila Nova (Seven Editora, 2025)
Oral cancer represents a serious public health problem, with high rates of morbidity and mortality, especially in developing countries. Although its early detection is decisive for prognosis, diagnosis still occurs in advanced stages in most cases. Primary Health Care (PHC), due to its capillarity and preventive nature, is the ideal scenario for the early identification of potentially malignant lesions and oral cancer. This article proposes an integrated approach among PHC professionals, emphasizing the importance of systematic clinical examination, health education, and continuing education. The methodology involved a narrative review of the literature in international and national databases, addressing early detection strategies, barriers faced in clinical practice, and current public policies. The results highlight the need for standardized protocols, specific training, and educational campaigns as pillars for the effectiveness of early diagnosis. The discussion emphasizes that strengthening PHC is essential to change the current epidemiological scenario of oral cancer in Brazil and in the world. DOI: https://doi.org/10.56238/sevened2025.018-008